Malignant melanoma in extrabulbar localization – selected clinical cases - Gotz-Więckowska, Anna; Bręborowicz, Danuta; Kocięcki, Jarosław (Contemporary Oncology/Współczesna Onkologia, 1999)
Conjunctival malignant melanoma in relatively rare entity, but – despite of often small dimensions – it may threaten patient’s eye and further life. The purpose of our study was presentation of our 4 patients suffering from extrabulbar melanocitic lesions with atypical and – in our opinion – interesting course, which were treated surgically in our Department. Patients and method : the group of 4 patients (4 eyes) consisted of 2 men and 2 women aged 60–68 years (mean – 63 years) were observed. Three patients underwent local tumor excision, which allowed to preserve the eyeballs, while in one case, because of large dimensions and very rapid growth – the exenteration had to be performed. Within entire group of patients only one of them was treated previously with another methods of therapy. Results : within evaluated group of patients only in one case the local recurrence of tumor was found 4 months after initial treatment. During the follow-up period no one of the patients developed generalization of the disease with metastases; conclusions: similar cases in appearance may present different clinical courses as well as diagnosis and may require different methods of treatment; surgical treatment is the method of choice and the possibility of preservation of the globe should be considered in each case as is shown by our follow-up; despite of a long-term course of the disease and different methods of treatment selected cases may not reveal metastases; each patient should be considered individually as to accuracy of diagnosis and the method of therapy.